Gender identity and research relationships - Ward, Michael Rhys Morgan (Studies in qualitative methodology ;, 2016)
Many researchers in recent years have begun to reflect on their gender identity and how this impacts on the research process and discuss how this helps build rapport with participants and creates successful or unsuccessful pieces of qualitative research. However, how does this intersect with other forms of identity, such as class, ethnicity, disability, age, sexuality? In this volume contributors explore these issues by reflecting on their own studies and research careers and address how important or unimportant gender has been in building research relationships. While the gender identity of the respondent/researcher relationship is undoubtedly important, what must also be acknowledged are the attributes which create a good fieldworker and competent social science researchers capable of understanding and engaging in different social situations and thought interaction with different participants.